2021
DOI: 10.1093/mutage/geab011
|View full text |Cite
|
Sign up to set email alerts
|

NEK1 deficiency affects mitochondrial functions and the transcriptome of key DNA repair pathways

Abstract: Previous studies have indicated important roles for NIMA-related kinase 1 (NEK1) in modulating DNA damage checkpoints and DNA repair capacity. To broadly assess the contributions of NEK1 to genotoxic stress and mitochondrial functions, we characterized several relevant phenotypes of NEK1 CRISPR knockout (KO) and WT HAP1 cells. Our studies revealed that NEK1 KO cells resulted in increased apoptosis and hypersensitivity to the alkylator methyl methanesulfonate, the radiomimetic bleomycin, and UVC light, yet incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 73 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…Finally, other NEK family members are associated with mitochondrial homeostasis and dynamics. NEK1 deficiency is related to abnormal mitochondrial functions and elevated ROS levels [ 60 ] while NEK4 deficiency leads to altered mitochondrial morphology and reduced mitochondrial respiration [ 61 ]. Consequently, there is overlap in the NEK5-associated pathways identified and those linked to other family members, indicating that that this kinase family must regulate critical biological processes in a concerted and integrated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other NEK family members are associated with mitochondrial homeostasis and dynamics. NEK1 deficiency is related to abnormal mitochondrial functions and elevated ROS levels [ 60 ] while NEK4 deficiency leads to altered mitochondrial morphology and reduced mitochondrial respiration [ 61 ]. Consequently, there is overlap in the NEK5-associated pathways identified and those linked to other family members, indicating that that this kinase family must regulate critical biological processes in a concerted and integrated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Nek4 has been previously detected in mitochondrial fractions, and it has been proposed that it may interact with several mitochondrial proteins [10]. Based on this observation, and that other members of the Nek family show effects on mitochondria [13][14][15][16][17][18][19], we decided to investigate the effects of Nek4 on mitochondrial respiration. Nek4.1 Flag expressing cells showed an increase in basal or in ATP-coupled respiration (Fig.…”
Section: Nek4 Accelerates Mitochondrial Respiration and Mitochondrial...mentioning
confidence: 99%
“…For some Nek family members, a role in mitochondria has already been shown [13][14][15][16][17][18][19], and for Nek1, a mitochondrial substrate, VDAC, was characterized [13]. As different members of the Nek family often show different and sometimes even opposite functions, we decided to investigate the role of Nek4 in this organelle, too.…”
Section: Introductionmentioning
confidence: 99%
“…Nek1 also contributes to mitochondrial functions. Nek1 deficiency can alter mitochondrial functions as it is associated with phenotypes of reduced mitophagy, increased number of mitochondria, and increased mitochondrial reactive oxygen species (ROS) [ 59 ]. Studies found that the activation of Nek1 by TLK1 contributes to the stability of Voltage Dependent Anion Channel 1 (VDAC1) and thus to mitochondrial permeability and integrity [ 60 ].…”
Section: Mammalian Nek1mentioning
confidence: 99%